Barriers to radiotherapy utilization: Consumer perceptions of issues influencing radiotherapy‐related decisions. Issue 5 (30th August 2016) - Sundaresan, Puma; King, Madeleine; Stockler, Martin; Costa, Daniel; Milross, Christopher
Abstract: Aims: Radiation therapy (RT) is an essential and cost‐effective cancer treatment, but it is underutilized in Australia. We aimed to quantify consumers' perceptions of factors that influence RT decisions. Methods: A cross‐sectional, survey‐based study was conducted in March–August 2012. Potential participants were invited to complete an electronic survey disseminated through multiple patient support and advocacy groups throughout New South Wales (NSW), Australia. Study invitations were also placed in local newspapers across NSW with hard copy surveys mailed to respondents. Current or past cancer patients (and carers) who had been offered RT were eligible to participate regardless of their RT decision. Results: Of the 1191 participants (electronic, n = 1153; hard copy, n = 38), 91% were female, most (88%) were current or past patients, and 78% had accepted RT. Issues commonly perceived to be moderate to strong influencers of RT decisions were: concern about acute and long‐term side effects; management of side effects; fear and anxiety regarding RT; lack of awareness of RT; lack of local availability of RT; and lack of RT information resources. Those who declined RT were significantly more likely to highlight practical difficulties with receiving RT. Conclusions: Although availability of RT is well recognized, other issues such as fear and anxiety about RT and perceived side effects appear to feature prominently in consumers' decisions. Perceived practical difficulties with receiving RT may have influenced those who declined RT. There may be a need for information resources, support services and interventions to increase awareness of RT.